Adaptive PID Type Iterative Learning Control - Sara Zamiri; Ali Madadi; Hamid-Reza Reza-Alikhani (Institute of Advanced Engineering and Science, 2014)
In this paper, an adaptive PID-type iterative learning control scheme is proposed for tracking problem in repetitive systems with unknown parameters. In this scheme, we use a combination of an optimal PID-type iterative learning controller and progection like adgusting algorithm that is based on tracking error which decreases by iterations increment. Layapunov method is used for convergence analysis of the presented scheme, and convergence condition is obtained in term of algorithm step size range. the effectiveness of proposed technique is illustrated by simulation results.DOI:http://dx.doi.org/10.11591/ijece.v4i6.6432